Immersive insights: evaluating augmented reality interfaces for pedestrians in a CAVE-based experiment - Tabone, Wilbert; Happee, Riender; Yang, Yue; Sadraei, Ehsan; García de Pedro, Jorge; Lee, Yee Mun; Merat, Natasha; de Winter, Joost (Frontiers in Virtual Reality, 2024)
Augmented reality (AR) has been increasingly studied in transportation, particularly for drivers and pedestrians interacting with automated vehicles (AVs). Previous research evaluated AR interfaces using online video-based questionnaires but lacked human-subject research in immersive environments. This study examined if prior online evaluations of nine AR interfaces could be replicated in an immersive virtual environment and if AR design effectiveness depends on pedestrian attention allocation. Thirty participants completed 120 trials in a CAVE-based simulator with yielding and non-yielding AVs, rating AR interface intuitiveness and crossing the road when safe. To emulate visual distraction, participants had to look into an attentionattractor circle that disappeared 1 second after the AR interface appeared. The results showed that intuitiveness ratings from the CAVE and previous online study correlated strongly (r ≈ 0.90). Head-locked interfaces and familiar designs (augmented traffic lights, zebra crossing) yielded higher intuitiveness scores and quicker crossing initiations than vehicle-locked interfaces. Vehicle-locked interfaces were less effective when the attention-attractor was on the environment's opposite side, while head-locked interfaces were relatively unaffected by attention-attractor position. In conclusion, this 'AR in VR' study shows strong congruence between intuitiveness ratings in a CAVE-based study and online research, and demonstrates the importance of interface placement in relation to user gaze direction.